Characterization of Donut-Like SrMoO4 Produced by Microwave-Hydrothermal Process. (31st October 2013) - Wannapop, Surangkana; Thongtem, Titipun; Thongtem, Somchai
Abstract : SrMoO4 hierarchical nanostructures were successfully produced by a one step of 270 W microwave-hydrothermal process of one of the solutions containing three strontium salts [Sr(NO3 )2, Sr(CH3 CO2 )2, and SrCl2 ·6H2 O] and (NH4 )6 Mo7 O24 ·4H2 O for different lengths of time. The as-produced products were characterized by X-ray diffraction, electron microscopy, and spectroscopy. In this research, they were primitive tetragonal structured donut-like SrMoO4, with the main 881 cm − 1   ν 1 ( A g ) symmetric stretching vibration mode of [ MoO 4 ] 2 − units and 3.92 eV energy gap.